Effectiveness of Student-Centered Instructional Strategies in Physical Education on Learners’ Physical Fitness and Engagement - MARK BENNETTE M. ULEP (The Bioscan, 2024)
This study examined the effectiveness of student-centered instructional strategies in Physical Education on learners’ physical fitness and engagement. Physical Education plays a crucial role in promoting active lifestyles, yet traditional teacher-centered approaches often limit learners’ participation and motivation. Using a quantitative quasi-experimental research design with a pretest–posttest approach, the study investigated whether student-centered strategies could improve learners’ physical fitness outcomes and levels of engagement. Participants were learners enrolled in Physical Education classes who were exposed to student-centered instructional strategies, such as cooperative learning, task-based activities, and peer interaction, over an eight-week period. Data were collected using standardized physical fitness tests measuring cardiovascular endurance, muscular strength, and flexibility, as well as a validated learner engagement questionnaire assessing behavioral, emotional, and cognitive engagement. Descriptive statistics and paired t-tests were used to analyze changes in physical fitness, while engagement levels were examined using mean scores and interpretations. Results showed significant improvements in all physical fitness components after the implementation of student-centered instructional strategies. Learners also demonstrated high levels of engagement across all engagement dimensions, indicating increased motivation, enjoyment, and active participation in Physical Education classes. The findings suggest that student-centered instructional strategies are effective in enhancing both physical fitness and learner engagement. By actively involving learners in the learning process, these strategies promote meaningful participation and sustained physical activity. The study concludes that adopting student-centered approaches in Physical Education can support learners’ holistic development and contribute to more effective and engaging PE instruction. Keywords student-centered instruction, physical education, physical fitness, learner engagement, quasi-experimental study